2020
DOI: 10.1016/j.jcyt.2020.04.099
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiltration of growth media supplemented with human platelet lysates for pathogen-safe xeno-free expansion of mesenchymal stromal cells

Abstract: Background aims: Human platelet lysate can replace fetal bovine serum (FBS) for xeno-free ex vivo expansion of mesenchymal stromal cells (MSCs), but pooling of platelet concentrates (PCs) increases risks of pathogen transmission. We evaluated the feasibility of performing nanofiltration of platelet lysates and determined the impact on expansion of bone marrowÀderived MSCs. Methods: Platelet lysates were prepared by freeze-thawing of pathogen-reduced (Intercept) PCs suspended in 65% storage solution (SPP+) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…Here we observed that WJ-MSC expanded in hPL enhanced their proliferative capacity, observing an increase of 33.3% in PD and consequent reduction of PDT (by 38.1%), as compared to WJ-MSC expanded in hS or FBS. Several studies described mixed proliferation rates of different MSC types following hPL supplementation [ 13 , 22 , 31 , 33 ]. In particular Kandoi et al evidenced significantly faster cell growth of umbilical cord tissue-derived MSC in hPL-enriched cultures, reaching PDT of 20.95 h vs. PDT in FBS [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here we observed that WJ-MSC expanded in hPL enhanced their proliferative capacity, observing an increase of 33.3% in PD and consequent reduction of PDT (by 38.1%), as compared to WJ-MSC expanded in hS or FBS. Several studies described mixed proliferation rates of different MSC types following hPL supplementation [ 13 , 22 , 31 , 33 ]. In particular Kandoi et al evidenced significantly faster cell growth of umbilical cord tissue-derived MSC in hPL-enriched cultures, reaching PDT of 20.95 h vs. PDT in FBS [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the inclusion of techniques that lead to pathogen inactivation without altering the characteristics of hPL is vital to produce GMP grade supplements. Recently, protocols for pathogen inactivation including solvent/detergent, photoinactivation or nanofiltration technology have been tested, proving to be innocuous for the prepared hPL in terms of factors composition and mechanism of action [ 12 , 13 ]. In that regard, one of the limitations of the present study deals with the absence of methodologies for pathogen inactivation and their impact on the stability of soluble factors present in hPL batches and the biological activity of WJ-MSC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, platelet lysates have demonstrated the advantages of replacing fetal bovine serum (FBS) for culturing various types of cells, including stem cells, fibroblasts and endothelial cells [ 1 , 12 ]. The use of HPL in cell culture is desired for clinical use by circumventing the risks of xeno-immunization against bovine antigens and the transmission of zoonotic diseases [ 13 , 14 ]. Moreover, the effect of HPL on directly promoting angiogenesis and tissue regeneration has been demonstrated [ 15 , 16 ], so HPL holds great promise for treating various tissue defects.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned studies employed fetal bovine serum (FBS) for ASC culture during cell sheet fabrication. However, due to the risks of xeno-immunization against bovine antigens, transmission of zoonotic diseases, and potential limits of availability, it was necessary to find suitable human alternatives for the manufacture of ASC sheets to meet clinical therapeutic purposes (Mackensen et al, 2000;Horwitz et al, 2002;Schallmoser and Strunk, 2013;Barro et al, 2020). Human platelet lysate (HPL) contains a number of mitogenic growth factors, including fibroblast growth factor (FGF), endothelial growth factor (EGF), platelet-derived growth factors (PDGF), vascular endothelial growth factor (VEGF), and transforming growth factor (TGF; Fekete et al, 2012;Chen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%